STRENGTHENING DATA-BASED OF INTERNAL QUALITY ASSURANCE SYSTEM THROUGH THE GROW COACHING APPROACH IN ELEMENTARY SCHOOLS - Desy Anita Karolina Sembiring; Afnani Toyibah; Ahmad Matinul Haq; Amir Rifa'i; Putri Ellen Gracia Risamasu; Rahmania Sadek; Rida Rimadani; Raden Bambang Sumarsono; Sunarni Sunarni (Mitra Mahajana: Jurnal Pengabdian Masyarakat, 2026)
The implementation of the Internal Quality Assurance System (SPMI/SPMI) at the elementary school level in Indonesia still faces structural challenges, including limited capacity in data-based quality mapping using the Education Report. This community service activity aimed to strengthen elementary school principals' and operators' capacity in implementing data-based SPMI through a coaching workshop using the GROW (Goal–Reality–Option–Will) framework. The activity was conducted on 4 May 2026 at SD Negeri 4 Dampit, Malang Regency, attended by 105 participants from 50 elementary schools. Implementation methods included material presentation on the SPMI concept, education quality mapping based on the Rapor Mutu Pendidikan, and a Focus Group Discussion (FGD) divided into four problem categories: literacy, numeracy, character, and learning quality. Evaluation was conducted using pre-test/post-test and qualitative analysis of FGD outcomes. Results indicated a significant improvement in participants' understanding, with the average score increasing from 76.44 to 87.42 on matched pairs (paired t-test t = 6.20; p < 0.001), Cohen's d = 0.73 (medium-to-large effect), and N-Gain = 0.42 (medium category). The proportion of participants in the "Excellent" category nearly doubled (22.1% to 43.3%), while the "Very Poor" category decreased significantly (18.6% to 4.4%). The FGD produced a problem mapping document and follow-up plan applicable to school-level quality improvement programs.